Analysis of Emotional Intelligence and Emotional Regulation Levels in Futsal Athletes - Nuzulfa Maisya Hasna; Pipit Pitriani; Mochamad Yamin Saputra (Universitas Negeri Semarang, 2025)
Futsal athletes frequently experience decreased concentration and increased technical errors when they are unable to regulate their emotions effectively under high competitive pressure. The fast-paced nature of futsal, combined with limited space, intense physical contact, and rapid decision-making demands, places significant psychological stress on athletes. Emotional intelligence is considered a key psychological factor that may support athletes in managing their emotional responses and maintaining optimal performance. This study aims to analyze the relationship between emotional intelligence and emotional regulation in futsal athletes. The research employed a descriptive correlational quantitative design. The sample consisted of 17 male futsal athletes from the Indonesia University of Education, selected using purposive sampling based on their status as experienced core players actively participating in competitions. Emotional intelligence was measured using the Trait Emotional Intelligence Questionnaire–Short Form (TEIQue-SF), consisting of 30 items rated on a 7-point Likert scale, while emotional regulation was assessed using the Emotion Regulation Questionnaire for Athletes (ERQ-A) 12 items. Data analysis utilized SPSS 29, including descriptive statistics, normality testing (Shapiro-Wilk), and Pearson correlation. Results showed emotional intelligence mean=3.37±0.53 (range: 2.33-4.33) and emotion regulation mean=47.20±5.10 (range: 38-55). Pearson correlation revealed significant positive relationship (r=0.722, p=0.018<0.05), rejecting H₀ and confirming strong correlation. Higher emotional intelligence predicted better emotion regulation, supporting adaptive strategies under futsal pressure. These findings confirm the need to integrate emotional intelligence training into futsal coaching programs to optimize performance, focus, and team dynamics in competitive settings.